Effect of adding freeze-dried black carrot powder on chemical and sensory properties of yoghurt (Damascus University Journal of agriculture sciences, 2023)
This research was carried out in the laboratories of the Department of Food Sciences at the Faculty of Agriculture - Damascus University, and it aimed to study the effect of adding different proportions of freeze-dried black carrot powder (0.25, 0.5, 0.75, 1%) on the chemical and sensory properties of yoghurt, where no significant change was observed in moisture and fat when the powder was added or when the percentage of addition was increased, while the addition of carrot powder led to an increase in the standard acidity of the processed yoghurt samples compared with the control. The syneresis of whey also decreased in the samples to which carrot powder was added, and this percentage decreased with the increase in the percentage of addition, When studying the biologically active substances (antioxidant activity, total phenols), it was noticed that the antioxidant activity and total phenols increased in yoghurt samples to which the freeze-dried black carrot powder was added, and they increased significantly with the increase in the percentage of addition, and the largest value of the antioxidant activity and total phenols was in the yoghurt added to it 1%. As for the sensory aspect, the addition of the powder led to a cohesive consistency in the curd, and the color of the yoghurt was affected by thecolor of the carrot powder, and the color became more clearer in the higher concentration. The addition of the powder did not affect the flavor of the yoghurt and slightly affected its acidity as a result of the increase in acidity. The best samples were the yoghurt samples added with 0.25 and 0.5% of the powder.
Keywords: Yoghurt; Freeze-Dried Black Carrot Powder; Chemical Indices; Sensory Properties